Quantifying Beta‐Galactosylceramide Kinetics in Cerebrospinal Fluid of Healthy Subjects Using Deuterium Labeling. Issue 6 (15th October 2016) - Kanhai, KMS; Goulooze, SC; Stevens, J; Hay, JL; Dent, G; Verma, A; Hankemeier, T; de Boer, T; Meijering, H; Chavez, JC; Cohen, AF; Groeneveld, GJ
Abstract : Therapeutics promoting myelin synthesis may enhance recovery in demyelinating diseases, such as multiple sclerosis. However, no suitable method exists to quantify myelination. The turnover of galactosylceramide (myelin component) is indicative of myelination in mice, but its turnover has not been determined in humans. Here, six healthy subjects consumed 120 mL 70% D2 O daily for 70 days to label galactosylceramide. We then used mass spectrometry and compartmental modeling to quantify the turnover rate of galactosylceramide in cerebrospinal fluid. Maximum deuterium enrichment of body water ranged from 1.5–3.9%, whereas that of galactosylceramide was much lower: 0.05–0.14%. This suggests a slow turnover rate, which was confirmed by the model‐estimated galactosylceramide turnover rate of 0.00168 day −1, which corresponds to a half‐life of 413 days. Additional studies in patients with multiple sclerosis are needed to investigate whether galactosylceramide turnover could be used as an outcome measure in clinical trials with remyelination therapies.